Introduction to computational mass transfer : with applications to chemical engineering - Yu, Kuo-Tsung; Yuan, Xigang (Heat and mass transfer,, 2016)
This book presents a new computational methodology called Computational Mass Transfer (CMT). It details a rigorous model for the simulation of concentration, temperature and velocity distributions in chemical and related processes.